Peran Afek Positif untuk Meningkatkan Dorongan Pembelian secara Impulsif pada E-Commerce Shopee (Jurnal Ekonomi dan Bisnis Islam, 2024)
AbstractThis research aims to determine the influence of review quality, source credibility, and observational learning on the urge to buy impulsively through positive affect on Shopee e-commerce users. This research was conducted on Generation Z Muslims in Jepara Regency who had made transactions on Shopee e-commerce. The number of respondents to this research was 150 people. The sampling method in this research used non-probability sampling with a purposive sampling technique. The data analysis technique used is Structural Equation Modeling (SEM) with the help of the AMOS 21.0 program. The results of this study show that review quality does not have a positive and significant effect on positive affect, while source credibility and observational learning have a positive and significant effect on positive affect. Apart from that, review quality, source credibility, and observational learning do not have a positive and significant effect on the urge to buy impulsively. This research implies that an entrepreneur in Shopee e-commerce must be able to maintain the quality of the goods sold, credible sources of information, and strategies to increase sales, because this can have a positive effect on consumers, thus encouraging them to buy impulsively.Keywords: Review Quality; Source Credibility; Observational Learning; Positive Affect; Urge to Buy Impusively.AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh review quality, source credibility, dan observational learning terhadap urge to buy impusively melalui positive affect pada pengguna e-commerce Shopee. Penelitian ini dilakukan pada generasi Z Muslim di Kabupaten Jepara yang telah bertransaksi di e-commerce Shopee. Responden penelitian ini berjumlah 150 orang. Metode penarikan sampel pada penelitian ini menggunakan non-probability sampling dengan teknik purposive sampling. Teknik analisis data yang digunakan adalah Structural Equation Modelling (SEM) dengan bantuan program AMOS 21.0. Hasil penelitian ini menunjukkan bahwa review quality tidak berpengaruh positif dan signifikan pada positive affect, sedangkan source credibility dan observational learning berpengaruh positif dan signifikan pada positive affect. Selain itu, review quality, source credibility, dan observational learning tidak berpengaruh positif dan signifikan pada urge to buy impusively. Implikasi pada penelitian ini adalah seorang pengusaha di e-commerce Shopee harus bisa menjaga kualitas dari barang yang dijual, sumber informasi yang kredibel, dan strategi peningkatan penjualan, karena hal tersebut dapat memberikan afek positif pada konsumen sehingga mendorong untuk membeli secara impulsif.Kata Kunci: Review Quality; Source Credibility; Observational Learning; Positive Affect; Urge to Buy Impusively.